(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In order to contain the spread of pandemic Covid- 19, most of the countries across the globe have come up with the contact tracing applications commonly known as “Contact Tracing Apps”. Transparency, privacy and security of user’s data are the major concerns that are associated with the successfulness of a contact tracing app. The success of a contact tracing app can be measured by looking at the segment of the population using the app. The Government of India launched Aarogya Setu as a mobile application to help to contain the spread of Covid- 19 by providing mechanisms to trace the contacts of an infected individual, so that the individuals who have come into the contact of an infected individual, can be isolated and quarantined as per the protocol issued by the government from time to time and thereafter can be medicated. Aarogya Setu Application serves as a preventive measure that one can take to keep himself/ herself informed, if the individuals whom he/ she has been in contact is not a Covid- 19 patient. Aarogya Setu is a technological endeavour undertaken by the Government of India that encompasses the software technology and internet technology. Majority of the countries across the world have adopted the technology based solutions for the purpose of contact tracing in the wake of Covid- 19.